Bezpečnost technických syst¨¦mů - Rotnágl, Pavel (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2009)
Tato diplomov¨˘ pr¨˘ce se zabýv¨˘ technickými syst¨¦my, jejich bezpečnost¨Ş a dalš¨Şmi požadavky na jejich jakost. Shrnut¨¦ poznatky o zm¨Şn¨§ných t¨¦matech jsou aplikov¨˘ny na konkr¨¦tn¨Ş oblast strojů ¨C na vysokonap¨§ťov¨¦ točiv¨¦ elektrick¨¦ stroje. Praktickou č¨˘st tvoř¨Ş analýza a hodnocen¨Ş diagnostických parametrů dvou typů uvedených strojů. Tato pr¨˘ce si d¨˘v¨˘ za c¨Şl předevš¨Şm hled¨˘n¨Ş souvislost¨Ş mezi bezpečnost¨Ş a technickou diagnostikou vysokonap¨§ťových točivých strojů. Dalš¨Şmi c¨Şly jsou nalezen¨Ş vhodn¨¦ metody analýzy diagnostikovaných parametrů a posouzen¨Ş strojů na z¨˘klad¨§ jejich výsledků. Př¨Şnosem t¨¦to diplomov¨¦ pr¨˘ce by m¨§ly být nov¨¦ myšlenky v posuzov¨˘n¨Ş vysokonap¨§ťových elektrických točivých strojů.

This thesis is focused on technical systems and evaluating their safety. It tries to make a complex view of links between safety, demands for quality and technical diagnostics. It tries to apply all the information about mentioned features to concrete branch of machines ¨C highŠ\voltage electrical rotary machines. Practical part of this thesis consists of statistical analysis of measured parameters by two hydroelectric generators. Main task of this thesis is to transpose theoretical knowledge of safety and technical systems to the branch of highŠ\voltage electrical rotary machines. This thesis also tries to find appropriate and more efficient evaluation method for analyzing the parameters of mentioned machines. Another benefit of this thesis should be bringing few new ideas about evaluating safety and technical status of highŠ\voltage electrical rotary machines. Keywords: technical system, safety, highŠ\voltage electrical machines, technical diagnostics
Safety of technological systems
Keywords: technický syst¨¦m; bezpečnost; točiv¨¦ elektrick¨¦ stroje; technick¨˘ diagnostika; technical system; safety; highŠ\voltage electrical machines; technical diagnostics